Luminescent property of CaWO4:Eu3+ nanophosphors prepared by molten salt synthesis. Issue 5 (11th April 2022) - Ding, Zhiqiang; Ding, Gongsheng; Fang, Ling; Peng, Zifei
Abstract: Red nanofluorescent materials based on CaWO4 :Eu 3+ were prepared by the molten salt method. Spherical CaWO4 particles with a size of 100 nm to 200 nm monodisperse sizes were prepared using different types of calcium salts. The KCl was chosen as the molten salt, under the same other experimental parameters, the obtained CaWO4 :Eu 3+ particles were more uniform, the diffraction properties were better. With a molar ratio of 15 for molten salt and Calcium salt, more spherical CaWO4 :Eu 3+ particles were produced small and sand homogeneous size. Using different amount of molten salt, it was found that the larger the amount of molten salt, the weaker the fluorescence property. Finally, by comparing the products obtained by the molten salt method with the solid state reaction method, it is found that the luminescence intensity of the products is 20% higher than that obtained by the solid state reaction method.